Latest Advancements in Next-Generation Semiconductors: Materials and Devices for Wide Bandgap and 2D Semiconductors - Wang, Zeheng; Huang, Jingkai (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This essential collection, edited by Dr. Zeheng Wang and Dr. Jing-Kai Huang, unveils the latest advancements in semiconductor technology that are considered to be the cornerstone of the modern digital era. Spanning cutting-edge research in semiconductor materials, devices, and systems, this reprint is an indispensable guide through the innovative realms of microelectronics and nanotechnology.Dive into expert discussions on device architectures, from high-electron-mobility transistors to innovative designs resistant to extreme conditions. Explore the frontiers of material science and fabrication techniques, witnessing groundbreaking methods that enhance device performance and reliability. Uncover the evolving landscape of energy efficiency and power management, crucial for next-generation telecommunications and electric vehicles. Lastly, immerse yourself in the dynamic world of optoelectronics, where advancements in light-based technologies are redefining possibilities.Bringing together pioneering research papers, this volume is not just an academic resource but a beacon for industry professionals and scholars alike, pointing the way to the future of semiconductor technology.